Evidence that abscisic acid mediates gene activation under dehydrating conditions in pearl millet - Qazi, Maimuna; Kota, Kambara; Gupta, Shashi K.; Takano, Tetsuo; Tsugama, Daisuke (Oxford University Press, 2025)
Pearl millet (Cenchrus americanus) is a drought-tolerant cereal crop. Differentially expressed genes (DEGs) were previously identified from multiple independent RNA sequencing (RNA-Seq) analyses of transcriptomes in dehydrated pearl millet plants. However, because such DEGs and their promoters were rarely compared between those independent analyses, upstream regulators of such transcriptomic changes remain unclear. Here, motifs in promoters of 68 sets of DEGs from publicly available 135 RNA-Seq data from unstressed and dehydrated leaves and roots were detected, which revealed that the majority of the sets of promoters of genes upregulated by such stresses contain abscisic acid (ABA) response elements. Genes potentially regulating ABA biosynthesis and signaling under such conditions were narrowed down by further analyzing the above data and newly obtained RNA-Seq data from ABA-treated plants and by reverse transcription-polymerase chain reaction. These results underscore the importance of ABA in pearl millet dehydration responses and the usefulness of promoter analyses.